Navigating career identity formation among Human Resource Development undergraduates in Malaysia: perspectives from the literature - Abd Rahim, Nur Aira; Mohd Zain, Masyitah; Mohd Anuar, Syaza Zahirah; Arbi Shukhair, Nur Sarah Alia; Mazlan, Aishah; Che Nawi, Nur Raihan (Faculty of Educational Studies, 2024)
Career identity is defined as the complex process of integrating multiple facets of one’s identity with evolving career roles, shaped by a combination of internal motivations and external influences. This study investigates the formation of career identity among undergraduate students pursuing Human Resource Development (HRD) careers at public universities in Malaysia, offering insights into how these students navigate career-related aspirations within the HRD field. Career identity formation is critical in professional development, especially in HRD, where a clear sense of self and purpose is essential to address dynamic organizational demands. The transition from secondary to tertiary education in Malaysia introduces unique challenges and opportunities, impacting how students conceptualize and solidify their career identities. This conceptual paper examines the breadth of existing literature, focusing on definitions, key theoretical frameworks, and diverse perspectives on career identity formation. By synthesizing relevant theories, this study aims to provide a comprehensive understanding of the forces shaping career identity in the Malaysian higher education context, underscoring the importance of targeted support to strengthen HRD students' professional self-concept and readiness for future roles.